Natural Language Processing and Chinese Computing 12th National CCF Conference, NLPCC 2023, Foshan, China, October 12-15, 2023, Proceedings, Part II - Liu, Fei.; Duan, Nan.; Xu, Qingting; Hong, Yu. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This three-volume set constitutes the refereed proceedings of the 12th National CCF Conference on Natural Language Processing and Chinese Computing, NLPCC 2023, held in Foshan, China, during October 12-15, 2023. The ____ regular papers included in these proceedings were carefully reviewed and selected from 478 submissions. They were organized in topical sections as follows: dialogue systems; fundamentals of NLP; information extraction and knowledge graph; machine learning for NLP; machine translation and multilinguality; multimodality and explainability; NLP applications and text mining; question answering; large language models; summarization and generation; student workshop; and evaluation workshop.
A Benchmark for Understanding Dialogue Safety in Mental Healt Support -- Fundamentals of NLP -- Span-based Pair-wise Aspect and Opinion Term Joint Extraction with Contrastive Learning -- Annotation Quality Measurement in Multi-Label Annotations -- Prompt-free Few-shot Learning with ELECTRA for Acceptability Judgment -- Dual Hierarchical Contrastive Learning for Multi-level Implicit Discourse Relation Recognition -- Towards Malay Abbreviation Disambiguation: Corpus and Unsupervised Model -- Information Extraction and Knowledge Graph -- Topic Tracking from Classification Perspective: New Chinese Dataset and Novel Temporal Correlation Enhanced Model -- A Multi-granularity Similarity Enhanced Model for Implicit Event Argument Extraction -- Multi-Perspective Feature Fusion for Event-Event Relation Extraction -- Joint Cross-Domain and Cross-Lingual Adaptation for Chinese Opinion Element Extraction -- A Relational Classification Network Integrating Multi-Scale Semantic Features -- A Novel Semantic-Enhanced Time-Aware Model for Temporal Knowledge Graph Completion -- Dual-Prompting Interaction with Entity Representation Enhancement for Event Argument Extraction -- Collective Entity Linking With Joint Subgraphs -- Coarse-to-Fine Entity Representations for Document-level Relation Extraction -- Research on Named Entity Recognition Based on Bidirectional Pointer Network and Label Knowledge Enhancement -- UKT: A Unified Knowledgeable Tuning Framework for Chinese Information Extraction -- SSUIE 1.0: A Dataset for Chinese Space Science and Utilization Information Extraction -- Extract then Adjust: A Two-Stage Approach for Automatic Term Extraction -- UniER: A Unified and Efficient Entity-Relation Extraction Method with Single-Table Modeling -- Multi-Task Biomedical Overlapping and Nested Information Extraction Model Based on Unified Framework -- NTAM: A New Transition-based Attention Model for Nested Named Entity Recognition -- Learning Well-separated and Representative Prototypes for Few-shot Event Detection -- Machine Learning for NLP -- A Frustratingly Easy Improvement for Position Embeddings via Random Padding -- IDOS: A Unified Debiasing Method via Word Shuffling -- FedEAE: Federated Learning Based Privacy-preserving Event Argument Extraction -- Event Contrastive Representation Learning Enhanced with Image Situational Information -- Promoting Open-domain Dialogue Generation through Learning Pattern Information between Contexts and Responses -- Neural News Recommendation with Interactive News Encoding and Mixed User Encoding -- Machine Translation and Multilinguality -- CD-BLI: Confidence-Based Dual Refinement for Unsupervised Bilingual Lexicon Induction -- A Novel POS-guided Data Augmentation Method for Sign Language Gloss Translation -- Faster and More Robust Low-Resource Nearest Neighbor Machine Translation -- Towards Effective Ancient Chinese Translation: Dataset, Model, and Evaluation -- Multimodality and Explainability -- Two-stage Adaptation for Cross-corpus Multimodal Emotion Recognition -- Knowledgeable Salient Span Mask for Enhancing Language Models as Knowledge Base -- A Text-Image Pair Is not Enough:Language-Vision Relation Inference with Auxiliary Modality Translation -- Enriching Semantic Features for Medical Report Generation -- Entity-related Unsupervised Pretraining with Visual Prompts for Multimodal Aspect-based Sentiment Analysis -- ZeroGen: Zero-shot Multimodal Controllable Text Generation with Multiple Oracles -- DialogueSMM: Emotion Recognition in Conversation with Speaker-aware Multimodal Multi-head Attention -- QAE: A Hard-label Textual Attack Considering the Comprehensive Quality of Adversarial Examples -- IMTM: Invisible Multi-Trigger Multimodal Backdoor Attack -- NLP Applications and Text Mining -- Enhancing Similar Case Matching with Event-Context Detection in Legal Intelligence -- Unsupervised Clustering with Contrastive Learning for Rumor Tracking on Social Media -- EP-Transformer: Efficient Context Propagation for Long Document -- Cross and Self Attention based Graph Convolutional Network for Aspect-based Sentiment Analysis -- KESDT: Knowledge Enhanced Shallow and Deep Transformer for Detecting Adverse Drug Reactions -- CCAE: A Corpus of Chinese-based Asian Englishes -- Emotionally-Bridged Cross-Lingual Meta-Learning for Chinese Sexism Detection -- CCPC: A Hierarchical Chinese Corpus for Patronizing and Condescending Language Detection -- FGCS: A Fine-grained Scientific Information Extraction Dataset in Computer Science Domain -- Improving Event Representation for Script Event Prediction via Data Augmentation and Integration -- Beyond Hard Samples: Robust and Effective Grammatical Error Correction with Cycle Self-Augmenting -- DAAL: Domain Adversarial Active Learning Based on Dual Features for Rumor Detection -- CCC: Chinese Commercial Contracts Dataset for Documents Layout Understanding -- Question Answering -- OnMKD: An Online Mutual Knowledge Distillation Framework for Passage Retrieval -- Unsupervised Clustering for Negative Sampling to Optimize Open-domain Question Answering Retrieval -- Enhancing In-Context Learning with Answer Feedback for Multi-Span Question Answering -- Large Language Models -- RAC-BERT: Character Radical Enhanced BERT for Ancient Chinese -- Neural Knowledge Bank for Pretrained Transformers -- Summarization and Generation -- A Hybrid Summarization Method for Legal Judgment Documents based on Lawformer -- Enhancing Semantic Consistency in Linguistic Steganography via Denosing Auto-Encoder and Semantic-Constrained Huffman Coding -- Review Generation Combined with Feature and Instance-Based Domain Adaptation for Cross-Domain Aspect-Based Sentiment Analysis -- WikiIns: A High-Quality Dataset for Controlled Text Editing by Natural Language Instruction -- Medical Report Generation based on Segment-Enhanced Contrastive Representation Learning -- Enhancing MOBA Game Commentary Generation With Fine-Grained Prototype Retrieval.
Keywords: Artificial intelligence; Artificial Intelligence